Association Between Serum Albumin And The Success Of Fluid Resuscitation In Children Hospitalizen In Cipto Mangunkusumo Hospital Burn Center - Dewi, Rismala; Kaltha, Karina; Wardhana, Aditya; Yanuarso, Piprim B. (Jurnal Plastik Rekonstruksi, 2018)
Background : Burn injury has a great impact on mortality and morbidity in children. Significant loss of albumin (hypoalbuminemia) in burn patient often leads to serious complications. However, it is still unclear whether serum albumin has a role in the success of fluid resuscitation in children with burn injury. Method : This is a retrospective cohort study based on medical record of children hospitalized with burn injury at Cipto Mangunkusumo Hospital Burn Centre from January 2012-March 2018. The subjects collected with the total sampling method. Result : Most burn injury happen because of scalds, and have grade 2 burn injury with PELOD score<10. Almost all subjects was succesfully resuscitated in the first 24 hour (95,1%). No association was found between the success of fluid resuscitation with either serum albumin [RR 1,175(95%CI 0,3-4,4) p=0,812], or with ureum, creatinin, lactate level, weight and the degree/extent of the burn injury. Conclusion: The success rate of fluid resuscitation in pediatric burn injury was quite high in Cipto Mangunkusumo Hospital Burn Centre. No association was found between serum albumin and the success of fluid resuscitation during the first 24 hour period. Keywords: albumin, burn, pediatric, resuscitation